Dinamika Manajemen Waktu Antara Praktikum Padat Dan Ibadah Tepat Waktu - Dalilul Falihin (CV. SINAR HOWUHOWU, 2026)
This study aims to examine in depth the dynamics of time management among engineering students in dealing with conflicts between intensive laboratory practicum schedules and the obligation to perform prayers on time. The background of this research is based on the reality that practicum activities often take place over long durations and require full student engagement, which frequently coincides with prayer times, especially obligatory prayers, leading to psychological pressure and dilemmas in prioritizing academic demands and spiritual obligations. This study employs a qualitative approach using a library research method by analyzing relevant scientific literature. The results indicate that time conflicts are not caused by contradictions between science and religion, but rather by limitations in time management skills and the lack of an optimal academic system that supports balance between academic and spiritual activities. Worship, particularly prayer, plays an important role as a coping strategy in reducing academic stress, enhancing inner peace, and restoring students’ focus and cognitive readiness. In addition, the collective culture among engineering students, such as cooperation and mutual assistance, serves as a supporting factor in maintaining practicum activities while allowing space for worship. Therefore, strengthening time management skills, institutional support, and more flexible and inclusive academic policies are necessary to achieve an optimal balance between academic achievement and spiritual fulfillment.